Long-term effects of the Swedish congestion charges - Maria Börjesson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper summarises the state of research on the long-term effects of congestion charging in Stockholm and Gothenberg. Sweden's two largest cities introduced time-of-day dependent, cordon-based congestion charging systems in 2006 and 2013. Public support for congestion charging initially increased following the introduction, but then slightly declined after a revision of the systems. While travel demand in Stockholm has become more price sensitive over time, the reverse happened in Gothenburg. The study examines the reasons behind these findings and discusses policy implications.
Keywords: 330